2018
DOI: 10.25258/ijpqa.v9i4.14537
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Evaluation on Oral Antidiabetic Drug Use: A Study of Effectiveness, Safety and Patient Adherence in Surabaya Primary Health Care

Abstract: Medication non-adherence is one of the biggest causes of leftover medicines. Up to 50% of patients worldwide do not take their prescribed medicines as recommended. Optimising the use of medication is beneficial to improving clinical outcomes for patients with chronic disease. Purpose: The aim of this study was to determine the effectiveness and safety of drug therapy, evaluate patient adherence, and identify of the patient's non-adherence behavior for oral antidiabetic drugs (OADs). Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…A minority of studies reported on a holistic approach, 15% (n = 16) in quantitative research and 19% (n = 7) in qualitative research. This approach was evidenced by the elicitation of patient’s medication experiences associated with drug-related problems, diseases or the provision of services [ 90 , 106 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. As part of the pharmaceutical care process or as criteria for the provision of CMM services, demographic data, psychosocial variables and physical and psychological quality of life scales were analysed [ 56 , 89 , 107 , 109 , 112 , 128 , 138 , 139 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minority of studies reported on a holistic approach, 15% (n = 16) in quantitative research and 19% (n = 7) in qualitative research. This approach was evidenced by the elicitation of patient’s medication experiences associated with drug-related problems, diseases or the provision of services [ 90 , 106 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. As part of the pharmaceutical care process or as criteria for the provision of CMM services, demographic data, psychosocial variables and physical and psychological quality of life scales were analysed [ 56 , 89 , 107 , 109 , 112 , 128 , 138 , 139 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are a small number of studies that gauge the patient’s medication experiences through open-ended questions [ 91 , 107 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. Oliveira et al suggest balancing the objective and subjective elements of patient care process in CMM services [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pemakaian terapi kombinasi mempunyai jumlah yang lebih tinggi dibanding dengan pemakaian terapi tung- Penelitian ini menunjukkan bahwa permasalahan dari kepatuhan dan ketercapaian target pengobatan pasien T2DM adalah kurang maksimal dalam sarana pelayanan kesehatan oleh tenaga kesehatan dan kurang kesadaran serta motivasi dari pasien sendiri. Hal ini diperkuat oleh peneliti sebelumnya yaitu Aditama et al, yang menyatakan bahwa kepatuhan dipengaruhi oleh beberapa faktor di antaranya efektifitas dan keamanan terapi obat, evaluasi kepatuhan pasien, dan identifikasi perilaku ketidakpatuhan pasien terhadap obat anti diabetes (OAD), serta peran aktif apoteker sebagai tenaga kesehatan yang bertugas memberi perawatan dan pelayanan kesehatan kepada pasien DM [8,9]. Target pengobatan DM tipe 2 yang berupa penurunan GDP belum mencapai hasil yang maksimal.…”
Section: Pembahasanunclassified